Perspective: Biochemical and Physical Constraints Associated With Preparing Thin Specimens for Single-Particle Cryo-EM - Han, Bong-Gyoon; Armstrong, Max; Fletcher, Daniel A.; Glaeser, Robert M. (Frontiers in Molecular Biosciences, 2022)
While many aspects of single-particle electron cryo-microscopy (cryo-EM) of biological macromolecules have reached a sophisticated level of development, this is not yet the case when it comes to preparing thin samples on specimen grids. There currently is considerable interest in achieving better control of both the sample thickness and the amount of area that is useful, but that is only one aspect in which improvement is needed. This Review addresses the further need to prevent the macromolecular particles from making contact with the air-water interface, something that can result in preferential orientation and even structural disruption of macromolecular particles. This unwanted contact can occur either as the result of free diffusion of particles during the interval between application, thinning and vitrification of the film of remaining buffer, or – when particles have been immobilized – by the film of buffer becoming too thin prior to vitrification. An opportunity now exists to apply theoretical and practical insights from the fields of thin-film physical chemistry and interfacial science, in an effort to bring cryo-EM sample preparation to a level of sophistication that is comparable to that of current data collection and analysis.